Challenging Management in Work-Related Eye Injuries: A Case Report of Steam Boiler Explosion-Induced Open Globe Injury: Poster Presentation - Case Report - Resident - Rifhani Atthaya Putri; Rodiah Rahmawaty Lubis (Majalah Oftalmologi Indonesia, 2023)
Introduction : Work-related eye injuries (WREIs) are major health problems leading to vision loss worldwide. In this study, we reported a case of WREIs from blast injury caused by a steam boiler explosion Case Illustration : A 55-year-old male, laundry worker presented to the emergency unit with pain, bleeding, and sudden vision loss in the left eye, 8-hours after a blast injury from steam boiler. He was conscious with normal vital signs. He had lacerations to his left eyelid, frontal, and temporoparietal. Ocular examination revealed a visual acuity of no light perception, full-thickness laceration of the lower eyelid and inferior canalicular, diffuse subconjunctival hemorrhage, corneoscleral laceration with choroidal expulsion, and active bleeding. On investigation, B-scan ultrasonography revealed vitreous hemorrhage and CT scan showed no orbital fracture. He underwent evisceration, eyelid reconstruction, and lacrimal canaliculi repair surgery under general anesthesia and planned to custom-made ocular prosthesis. Discussion : WREIs include eyeball injuries, eye adnexa injuries, eyelid lacerations, and orbital wall fractures that occur during work-related activities. The incidence of WREIs is higher in men aged 20-40 years. In this case, the patient presented with an open globe injury resulting in sudden vision loss, requiring urgent surgical intervention to prevent further complications. Ocular prostheses can provide acceptable aesthetics and improve the patient's quality of life by helping them to integrate into society. Conclusion : WREIs can lead to permanent vision loss and require urgent surgical intervention. Employers must prioritize workplace safety by providing adequate training and appropriate eye protection such as safety goggles to minimize the risk of eye injuries.